2010
DOI: 10.1287/trsc.1090.0289
|View full text |Cite
|
Sign up to set email alerts
|

Ground Delay Program Planning Under Uncertainty Based on the Ration-by-Distance Principle

Abstract: This paper presents ration-by-distance (RBD), a new allocation method to be used in planning ground delay programs (GDPs) for Traffic Flow Management. It is shown that RBD minimizes total expected delay, under certain assumptions related to the manner in which GDP's are dynamically controlled. On the other hand, RBD taken to the extreme has poor characteristics with respect to the equity of the allocation it produces. To address this issue, we propose a constrained version of RBD as a practical alternative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 16 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Even if this is not always true, since the GDP has shifted the demand, the natural spread of flights times and schedules seems to allow traffic management to use this criterion quite extensively in practice. This assumption is similar to the cancellation policies defined in Ball et al (2010).…”
Section: Ground Delay Programs Data Samplementioning
confidence: 92%
“…Even if this is not always true, since the GDP has shifted the demand, the natural spread of flights times and schedules seems to allow traffic management to use this criterion quite extensively in practice. This assumption is similar to the cancellation policies defined in Ball et al (2010).…”
Section: Ground Delay Programs Data Samplementioning
confidence: 92%
“…Different from the traditional ground delay program, the distance-based program only includes a set of flights whose origin airports are near the destination airport. In Ball, Hoffman, and Mukherjee (2010), the authors propose a novel ground delay program based on the ration-by-distance principle, in which the ground delay program tends to delay the flights departing from near airports instead of the flights from the far airports. Trani (2003, 2006) of air traffic at the National Airspace System (NAS) through the development of the airspace planning and collaborative decision-making model (APCDM).…”
Section: Airspace Flow Managementmentioning
confidence: 99%
“…For example, under the collaborative decision-making initiative, the ration-by-schedule GDP has been widely used to equitably assign the arrival slot (Ball, Hoffman, and Mukherjee 2010;Vossen et al 2003). In Sherali, Smith, and Trani (2002); Trani (2003, 2006); Sherali et al (2011), the equity concept has already been integrated in the APCDM for an airspace traffic flow program.…”
Section: Equity Consideration Among Airlinesmentioning
confidence: 99%
“…Goodhart looked at the incorporation of user preferences to the en route resource allocation process (Goodhart, 2000). As an alternative to the application of GDPs (and therefore, RBS) for en route resource allocation (Jakobovits et al, 2005), Hoffman et al (2007) and Ball et al (2010) introduced the Ration-by-Distance (RBD) allocation method. They demonstrated that RBD could be more efficient than RBS under early GDP cancellation, but less equitable.…”
Section: Introductionmentioning
confidence: 99%